Anak Putus Sekolah di Desa Teluk Jira Kecamatan Tempuling Kabupaten Indragiri Hilir - Ceria Defnanda; Indrawati Indrawati (Jurnal Ilmiah Dikdaya, 2025)
School dropouts are a social phenomenon in which a school-aged child stops attending school or no longer receives formal aducation in a school setting. There are 25 school-aged children who have dropped out of elementary school in Teluk Jira Village Tempuling Subdistrict Indragiri Hilir Regency from 2019 to 2023. This study was conducted to understand the family profiles of dropout children and to identify the causes of school dropouts. Using a qualitative research method, the study was carried out in Teluk Jira Village with the research subjects being the families of dropout children, and the sample selection was done using purposive sampling. Data collection techniques included interviews, observation, and documentation, while data analysis techniques involved data reduction, data presentation, and conclusion drawing. The results revealed that the families of dropout children in Teluk Jira Village are from lower-middle socioeconomic backgrounds, with an average education level of not completing elementary school, and working as farmers or farm laborers. There are six factors contributing to school dropouts in Teluk Jira Village: poverty, lack of parental support, low learning motivation, difficult access to school, laziness, and peer influence.